Estudio sobre acceso al servicio de acueducto en Quibdó-Chocó, Colombia (2016)
"With the strategic geographical location and the environmental conditions of humid tropics, Quibdó, presents high levels of annual precipitation. So, traditionally the main source of water use, is rainwater. In these conditions, and the weight of being surrounded by large rivers and its affluents (Atrato, Cabí, Cascorba, La Yesca, etc), only 33% of the population has access to the aqueduct... However, there is a high risk in the functional future of the aqueduct, since the interests and the cultural, social and economic characteristics of the population were not considered. This increases the likelihood that the system may face major problems that affect and obstruct service delivery." -- Tomado del Formato de Documento de Grado.